"And I was there" Pearl Harbor and Midway--breaking the secrets - Layton, Edwin T.; Pineau, Roger, 1916-; Costello, John. (New York : W. Morrow, 1985)
Pearl Harbor. 7 December 1941. Japanese bombs and torpedoes slam into the battleships of the Pacific Fleet as Commander Edwin T. Layton leaps up the stairs to his second-floor office. He looked out the window to see Oklahoma upside down and Arizona ablaze. Why did the Japanese attack? What had gone wrong? This is the first book by a top-ranking American navy officer to answer these questions. Admiral Layton scrupulously kept these secrets to himself - for forty-three years - until recently, when the government released half a million classified documents from its intelligence archives. Only then did Layton believe he was free to tell his story. He names those who knew about the Japanese intentions, and how they misused it. --from inside jacket.
Includes index.
Bibliography: p. 570-581.
71079
Keywords: Layton, Edwin T., -- 1903-1984; United States. -- Navy -- Biography; Pearl Harbor (Hawaii), Attack on, 1941 -- Personal narratives, American; Midway, Battle of, 1942 -- Personal narratives, American; Admirals -- Biography. -- United States